DEMAND FORECASTING IN THE PHARMACEUTICAL MARKET AND VISUAL ANALYTICS METHODOLOGY IN BUSINESS INTELLIGENCE SYSTEMS (Uzbekistan Open Conference, 2025)
This article explores the methodology of using Business Intelligence (BI) systems for identifying and forecasting demand for pharmaceutical products in the market. The study incorporates historical data analysis, seasonal factors, climatic conditions, epidemiological situations, and economic indicators into the forecasting process. Furthermore, the paper examines how BI systems, through visual analytics tools, enable monitoring of demand dynamics for pharmaceutical goods and facilitate real-time decision-making. The results of the research demonstrate that the use of BI systems increases the accuracy of sales forecasting, optimizes inventory levels, and enhances overall business efficiency.